Relationship Stability: Evidence from Labor and Marriage Markets - Iris Kesternich; Bettina Siflinger; James P. Smith; Franziska Valder (CESifo GmbH, 2024)
Based on a sample of elderly individuals from the Survey of Health, Ageing, and Retirement in Europe, we investigate the relationship between job and marital stability over the life cycle. We argue that an unobserved, time-varying social skill affects stability in both markets. Using a grouped fixed-effects estimator, we show that unobserved relationship stability in both markets is significantly and positively associated. Instability in both markets is associated with lower levels of trust and conscientiousness and higher levels of extraversion and neuroticism. The absence of the father during childhood perpetuates higher instability later in life. Higher instability is also costly since it is associated with lower levels of late-life well-being.
Keywords: J12; J24; J63; I31; C33; 330; relationship stability; marriage dissolution; job turnover; social skills; non-cognitive skills; grouped fixed-effect estimator; survey of health; ageing and retirement in Europe